ANALISIS PERMASALAHAN KREDIT MACET PADA CREDIT UNION YOS SUDARSO AMBULU - Ricko Mahhendra Kusuma; Siska Putri Aprilia; Mochammad Febrianto; Sampir Andrean Sukoco (Tamilis Synex: Multidimensional Collaboration, 2024)
This research focuses on how to find out the problem of bad credit at CU Yos Sudarso in 2024. This research was carried out using the Qualitative Descriptive Analysis method sourced from primary and secondary data through interviews and documentation. The informants in this research included the treasurer, administrative and educational staff and CU Yos Sudarso employees. The research results show that the Analysis of Bad Credit Problems at CU Yos Sudarso is caused by internal and external factors. Internal factors found include cooperatives' poor ability to analyze credit applications, deficiencies in human resource management, and ineffective loan interest rates. External factors found include failures/accidents that befell customers and credit loans without the family's knowledge. This research shows that CU Yos Sudarso needs to improve its credit analysis and human resource management capabilities to reduce bad loans. Apart from that, CU Yos Sudarso also needs to pay attention to external aspects such as failures/accidents and credit loans without the family's knowledge to reduce the risk of bad credit.